the trumpet of the swan - Marcellino, Fred; Fred Marcellino (Harpercollins Children's book, 1970)
Like the rest of the his family, louis is a trumpeter swan. But unlike his four brothers and sisters, louis can't trumpet joyfully. In fact, he can't even make a sound. And since he can't trumpet his love, the beautiful swan serena pays absolutely no attention to him. Louis tries everything he can think of it to win serena's affection he even goes to school to learn to read and write. But nothing seems to work. then his father steals him a real brass trumpet.